THE IMPLEMENTATION OF PARALLEL-TEAM TEACHING IN TEACHING SPEAKING AT ENGLISH EDUCATION PROGRAM OF MAKASSAR STATE UNIVERSITY - Akbar, Muhammad (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2017)
The objectives of this research were: (1) to find out whether or not the use of parallel-team teaching improves the students’ speaking skill and (2) to find out whether or not the students are interested in joining the speaking class through parallel-team teaching. This research employed a quasi-experimental design. The sample consisted of 40 students of second-semester students of English Education Program of Makassar State University, in academic year 2016/2017. The research data were collected by using two kinds of instruments: the speaking test for the students’ speaking skill and questionnaire for students’ interest.  Data on the students’ speaking skill were analyzed using descriptive and inferential statistics, and data on the students’ interest were analyzed using the Likert scale. The results of the research were: (1) the use of parallel-team teaching in teaching speaking improved the students speaking skill, (2) the use of parallel-team teaching increased the students’ interest in joining the speaking class.  It can be concluded that the use of Parallel-Team Teaching is effective to be implemented in improving the students’ speaking skill in terms of accuracy, fluency, comprehensibility and content and the students have very high interest toward Parallel-Team Teaching in teaching speaking